Fire resistant design of offshore topside structures (Steel Construction Institute, 1993)
'Section 4 of the Interim Guidance Notes for the Design and Protection of Topside Structures against Explosion and Fire (IGN) gives design guidance for fire resistance. This Technical Note is intended to compliment that section in a number of subject areas and offers more commentary, particularly with regard to the analysis methods. Worked examples are also included. It is intended that this document should not duplicate the IGN, although for clarity it is inevitable that parts will. The scope of this document is only intended to cover the following sections of the IGN: Section 4.4 - Determination of Component Temperatures Section 4.6 - Response to Fire Effects"--Knovel.
"Technical note, no. 1, February 1993."
"Technical notes and worked examples to compliment the IGN's Technical Note on Fire resistant design of offshore topside structures."
Keywords: Drilling platforms -- Fires and fire prevention.; Offshore structures -- Fires and fire prevention.; Drilling platforms -- Design and construction.; Offshore structures -- Design and construction.; Steel, Structural -- Effect of high temperature on.; Steel, Structural -- Effect of explosion on.; Blast effect.; elektronické knihy; electronic books